Biodiversity conservation or indigenous people's welfare: A dilemma for forest management in Vietnam's Bu Gia Map National Park. Issue 4 (8th August 2019) - Nguyen, Toai; Lawler, Susan; Goldoftas, Barbara; Le, Chi
ABSTRACT: This study examined the interactions between the socioeconomic factors of indigenous people and their dependency on forest products collected from Vietnam's Bu Gia Map National Park. Sixty indigenous households were interviewed about their income, education, land area and status, cultural expenses, periods of insufficient food supply, and the frequency of trips to the national park. The results show that insufficient food supplies, the area of land owned by respondents, expenses related to cultural activities such as weddings, and the efficiency of land use significantly correlated with the levels of dependence of indigenous people on natural forests. Importantly, most respondents suffered from hunger for several months each year. This seasonal hunger correlates with their dependency on the national park. These socioeconomic factors can be targeted by park managers to resolve problems for indigenous people, creating positive outcomes for both human society and biodiversity conservation.